DOUBLE STANDARDS IN HATE COMMENTS AGAINST K-POP ARTISTS: PRAGMATICS STUDY - Rika, Atta (Universitas Mahaputra Muhammad Yamin, 2024)
This study aims to describe the forms of double standards in hate comments against K-POP artists found on Instagram. This research used a descriptive qualitative approach, which refers to research methods that produce descriptive data using a pragmatic approach. The data was collected from the most followed K-POP pages on Instagram in Indonesia: @fyi.korea, @officialkvibes, and @coppamagz. The objects of this study are the hate comments found on these Instagram pages. The theory used to analyze the data was speech act theory, which consists of locutionary, illocutionary, and perlocutionary. This was followed by the identification of double standards. Pragmatic coding specifically targets linguistic patterns that indicate double standards. Based on the results of observations on these sites, it was found that some of the data included hate comments aimed at several K-pop idols. The results of the study indicate that the topics that receive the most hate comments were related to dating scandals, the sexy appearance of K-Pop artists, and the physical appearance and visual aspects. Based on the results, the double standard towards the involved K-POP artists is glaringly obvious. It can be concluded that there were two main factors that contribute to this double standard: gender and popularity. In terms of gender, female K-POP artists are criticized and receive hate comments more often than their male counterparts. Meanwhile, in terms of popularity, K-POP artists who are more popular tend to receive more hate comments than those who are less popular.